(untitled) (West African Journal on Sustainable Development, 2024)
Background: The global demand for freshwater is increasing at an alarming rate, outpacing population growth. Access to safe water is a critical sustainable development issue, with 2.1 billion people worldwide and over half of the population in developing countries lacking a "safely managed" water supply. This study aimed to investigate the microbiological quality of preferred drinking water sources and its association with waterborne infections (WBIs) among households in Ebenebe, a rural community in Anambra State, Nigeria. Methodology: A cross-sectional descriptive survey and laboratory analysis were conducted among 504 households. Data on preferred drinking water sources, determinants, and symptoms of WBIs were collected using a questionnaire. Water and faecal samples were collected from randomly selected household members for laboratory analysis. Results: The findings revealed that borehole water (74%) was the most commonly accessed and preferred drinking water source. Borehole water samples contained 74.3% of all isolated bacteria, while spring and lake samples had the least (2.9%). Escherichia coli (295, 19%) was the most frequently detected bacterium, with no parasites seen. Faecal analysis showed that 427 respondents (85%) had WBIs, with those aged 15-64 years (332, 77.8%) and females (253, 59.3%) being the most affected. Helminthes were the most frequently detected parasite (203, 93%), and hookworm (81, 37%) was the most common parasite ova seen. Overall, E. coli was the most frequently isolated microorganism. However, the association between preferred drinking water sources and WBIs was not statistically significant. Conclusion: The preferred drinking water of households in Ebenebe contained pathogenic organisms capable of causing WBIs and diseases. Therefore, health education on user-friendly, point-of-use filtration and disinfection methods is recommended to improve the water quality and reduce the risk of WBIs and diseases.